Natural Fiber Reinforced Composites: A Review on Potential for Corrugated Core of Sandwich Structures - A. F., Jusoh; M. R. M., Rejab; Siregar, J. P.; Bachtiar, Dandi (EDP Sciences, 2016)
Natural fibers, characterized by sustainability, have gained a considerable attention in recent years, due to their advantages of environmental acceptability and commercial viability. In this paper, the characterization of natural fibers including the mechanical properties and alkalization of fibers is presented. Most recent study had gone through the mercerization process to improve the toughness of natural fibers; which is a well-known hydrophilic material. Traditional reinforcement method was commonly used to fabricate a natural fiber composite such as hand lay-up and mold press due to its convenience in terms of time and cost. Also, different kind of matrix material used in different kind of natural fibers gave high impact on the tensile and flexural test result. By selecting appropriate chemical treatment, matrix material and fabrication method, the tensile and flexural test gives different results and findings. As most researchers tend to use metals to create corrugated cores for sandwich structure, it is possible to develop this structure using natural fibers such as kenaf, wood dust, and other natural fibers.